New Marine Antifouling Compounds from the Red Alga Laurencia sp. - Yuko Oguri; Mami Watanabe; Takafumi Ishikawa; Takashi Kamada; Charles Santhanaraju Vairappan; Hiroshi Matsuura; Kensuke Kaneko; Takahiro Ishii; Minoru Suzuki; Erina Yoshimura; Yasuyuki Nogata; Tatsufumi Okino (2017)
Six new compounds, omaezol, intricatriol, hachijojimallenes A and B, debromoaplysinal, and 11,12-dihydro-3-hydroxyretinol have been isolated from four collections of Laurencia sp. These structures were determined by MS and NMR analyses. Their antifouling activities were evaluated together with eight previously known compounds isolated from the same samples. In particular, omaezol and hachijojimallene A showed potent activities (EC50 = 0.15–0.23 µg/mL) against larvae of the barnacle Amphibalanus amphitrite